USE OF PESTICIDES IN AGRICULTURAL PRODUCTION AND CASES OF NEOPLASIA IN THE POPULATION RESIDING IN THE HEALTH REGIONS OF RIO VERDE/GO AND MINEIROS/GO (2012–2022) (CIPEEX, 2025)
This article discusses the impacts of pesticide use on the health-disease process of populations exposed to agricultural practices, with emphasis on cancer development. The research is exploratory and uses secondary data from sources such as DATASUS to analyze notifications of exogenous pesticide intoxication. The study covers the period from 2012 to 2022 and focuses on the municipalities of Rio Verde/GO and Mineiros/GO. The results indicate an increase in soybean and sugarcane production in these municipalities. Regarding intoxication cases, a significant relationship can be inferred between exposure and acute manifestations, despite underreporting. Greater monitoring and follow-up are necessary to reach accurate conclusions about the chronic effects pesticides may cause.
Keywords: Agribusiness; Neoplasms; Public Health